Krisis Identitas Perempuan dalam Cerpen Ibu Karya Zulfah Nur Alimah - Septiani, Nur Alifah (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
omen in patriarchal societies are always confronted with social constructs that place the domestic sphere as the primary space for fulfilling their identity. This condition gradually obscures women's personal identities because their existence is more often interpreted thru their roles as wives and mothers. This study uses a descriptive qualitative method to reveal the identity crisis of women found in the short story